Comparative barrier membrane degradation over time: Pericardium versus dermal membranes. Issue 5 (5th May 2021) - Bornert, Fabien; Herber, Valentin; Sandgren, Rebecca; Witek, Lukasz; Coelho, Paulo G.; Pippenger, Benjamin E.; Shahdad, Shakeel
Abstract: Objective: The effectiveness of GBR procedures for the reconstruction of periodontal defects has been well documented. The objective of this investigation was to evaluate the degradation kinetics and biocompatibility of two resorbable collagen membranes in conjunction with a bovine xenograft material. Materials and Methods: Lower premolars and first molars were extracted from 18 male Yucatan minipigs. After 4 months of healing, standardized semi‐saddle defects were created (12 mm × 8 mm × 8 mm [ l˙̇ × W˙  ×  d ]), with 10 mm between adjacent defects. The defects were filled with a bovine xenograft and covered with a either the bilayer collagen membrane (control) or the porcine pericardium‐derived collagen membrane (test). Histological analysis was performed after 4, 8, and 12 weeks of healing and the amount of residual membrane evaluated. Non‐inferiority was calculated using the Brunner‐Langer mixed regression model. Results: Histological analysis indicated the presence of residual membrane in both groups at all time points, with significant degradation noted in both groups at 12 weeks compared to 4 weeks ( p  = .017). No significant difference in ranked residual membrane scores between the control and test membranes was detected at any time point. Conclusions: The pericardium‐derived membrane was shown to be statistically non‐inferior to the control membrane with respect to resorption kinetics and barrier function when utilized for guided bone regeneration in semi‐saddle defects in minipigs. Further evaluation is necessary in the clinical setting.